2020
DOI: 10.1021/acs.analchem.0c04269
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Affinity Ratiometric Quenching (DARQ) Assay for the Quantification of Therapeutic Antibodies in CHO-S Cell Culture Fluids

Abstract: More than 100 monoclonal antibodies (mAbs) are in industrial and clinical development to treat myriad diseases. Accurate quantification of mAbs in complex media, derived from industrial and patient samples, is vital to determine production efficiency or pharmacokinetic properties. To date, mAb quantification requires time and labor-intensive assays. Herein, we report a novel dual-affinity ratiometric quenching (DARQ) assay, which combines selective biorecognition and quenching of fluorescence signals for rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Binding‐induced fluorescence change in labeled Fc‐binding ligands has also been reported elsewhere (Aoyagi et al, 2003, 2002; Thompson et al, 2017; Turner et al, 2020); however, the longer response time and offline monitoring techniques used in these works make these approaches less attractive for column monitoring. We have demonstrated an approach for continuous human IgG detection by fluorescence intensity, using immobilized reporters, which can be reused at least 100 times.…”
Section: Conclusion and Future Perspectivessupporting
confidence: 52%
See 1 more Smart Citation
“…Binding‐induced fluorescence change in labeled Fc‐binding ligands has also been reported elsewhere (Aoyagi et al, 2003, 2002; Thompson et al, 2017; Turner et al, 2020); however, the longer response time and offline monitoring techniques used in these works make these approaches less attractive for column monitoring. We have demonstrated an approach for continuous human IgG detection by fluorescence intensity, using immobilized reporters, which can be reused at least 100 times.…”
Section: Conclusion and Future Perspectivessupporting
confidence: 52%
“…A total of 5 g/L human IgG in buffer A was loaded (1.25 ml/min) onto a prepacked 5 ml MabSelect SuRe protein A and the column effluent continuously flowed into a monitoring column as described above, while fluorescence was continuously monitored (Figure 5a). There has also been reported elsewhere (Aoyagi et al, 2003(Aoyagi et al, , 2002Thompson et al, 2017;Turner et al, 2020); however, the longer response time and offline monitoring techniques used in these works make these approaches less attractive for column monitoring. We have demonstrated an approach for continuous human IgG The approach could potentially be extended to other biopharmaceutical products such as non-Fc proteins and therapeutic viruses, and IgG monitoring also could find applications in bioreactor and membrane integrity monitoring.…”
Section: Continuous Monitoring Of Igg Breakthrough From An Upstream P...mentioning
confidence: 99%
“…Prior work introduced DARQ as a simple mix-andread assay for the quantification of therapeutic monoclonal antibodies Trastuzumab and Adalimumab�respectively used in fighting breast cancer and rheumatoid arthritis�in bioprocess fluids. 17 Our results showed that DARQ technology is endowed with numerous advantages compared to ELISA, BLI, and SPR assays (Table S1), 18−25 chiefly, high reproducibility, speed and ease of execution (mix-and-read), flexibility, robustness, and low cost of goods. This work demonstrates the application of DARQ technology to the quantification of anti-SARS-CoV-2 antibodies in a variety of complex samples.…”
Section: ■ Introductionmentioning
confidence: 89%
“…1,2 IMDs are being developed for drug delivery, 3 tissue regeneration 4 and biochemical sensing. 5 Despite their benefits, the application of IMDs has been forestalled by materials with inadequate mechanical properties, the risk of infection 1,2 and the need for removal surgery at the end of implant life. To overcome the limitations of traditional implants for short-term applications, a movement has emerged aiming at developing transient electronics that can dissolve or be degraded in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Implantable medical devices (IMDs) provide functions ranging from cardiac pacing to neurostimulation, and enable seamless physiological monitoring and therapeutic delivery 1,2 . IMDs are being developed for drug delivery, 3 tissue regeneration 4 and biochemical sensing 5 . Despite their benefits, the application of IMDs has been forestalled by materials with inadequate mechanical properties, the risk of infection 1,2 and the need for removal surgery at the end of implant life.…”
Section: Introductionmentioning
confidence: 99%